Thermal Performance of Coal-Fired Power Plant based on Number of Feedwater Heaters - Khaleel O.J.; Ibrahim T.K.; Ismail F.B.; Hassan S.H.A. (Penerbit Akademia Baru, 2023)
This study aims to investigate the feasibility of using a feedwater heaters system with coal-fired power plant. Furthermore, the influence evaluation of the different coal consumption on the coal-fired power plants in terms of power output and thermal efficiency improvements. As well, this study focuses on the effect of different feedwater heaters' numbers which caused the highest exergy destruction of the coal-fired power plants. For different values of the coal consumption, a parametric study was conducted to determine the efficiency of the coal-fired power plant. The results show that, when the coal consumption increases the power output will increases too. The slight decreases in the efficiencies are due to the small differences in how the mass flow rates of different streams increase. The exergy destruction was increased by about 16% when the consumption of fuel increases by 40 kg/s. It was observed that operating the coal-fired power plant at high coal consumption leads to reduce the effective ness of the feedwater heaters and increases the power output. 2022. Journal of Advanced Research in Fluid Mechanics and Thermal Sciences. All Rights Reserved.